2017
DOI: 10.1007/978-1-4939-6881-7_35
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of T Cell Immunological Synapses and Kinapses in Lymph Nodes

Abstract: T cells can become activated in lymph nodes following a diverse set of interactions with antigen-presenting cells. These cellular contacts range from short and dynamic to stable and long-lasting interactions, termed kinapses and synapses, respectively. Here, we describe a methodology to generate naïve T cells expressing a fluorescent probe of interest through the generation of bone marrow chimeras and to image T cell dynamics using intravital two-photon microscopy. In these settings, the formation of kinapses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…At different times after peptide injection (3, 24, 30, 48, and 72) lymph nodes were harvested and digested in RPMI with 1 mg/ml collagenase and 0.1 mg/ml DNase (Sigma) for 20 min at 37°C. Alternatively, mice were anesthetized and the popliteal lymph nodes prepared for intravital imaging as previously described ( Moreau and Bousso, 2017 ). In some experiments, a second cohort of OT-I CD8 + T cells labeled with 2.5 µM SNARF (Invitrogen) was adoptively transferred into mice by i.v.…”
Section: Methodsmentioning
confidence: 99%
“…At different times after peptide injection (3, 24, 30, 48, and 72) lymph nodes were harvested and digested in RPMI with 1 mg/ml collagenase and 0.1 mg/ml DNase (Sigma) for 20 min at 37°C. Alternatively, mice were anesthetized and the popliteal lymph nodes prepared for intravital imaging as previously described ( Moreau and Bousso, 2017 ). In some experiments, a second cohort of OT-I CD8 + T cells labeled with 2.5 µM SNARF (Invitrogen) was adoptively transferred into mice by i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the ability of B and T cells to move among strategic locations in the LN is critical to achieve a fully humoral response [ 31 ]. Two-photon laser microscopy has allowed to characterize B and T cell movement within the LN and has shown that lymphocytes move by a random walk [ 32 , 33 ]. In order to address whether the LN-on-a-chip supports cellular motility we analyzed in real time the movement of T and B immune cells by time-lapse microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…ton laser microscopy has allowed to characterize B and T cell movement w and has shown that lymphocytes move by a random walk [32,33]. In orde whether the LN-on-a-chip supports cellular motility we analyzed in real tim ment of T and B immune cells by time-lapse microscopy.…”
Section: Three-dimensional Lymph Node-on-a-chip Model To Study Cellular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation